DEVELOPING ENGLISH READING MATERIALS BASED ON LOCAL CONTENT FOR GRADE TENTH STUDENTS OF SMAN 10 MEDAN - Esra Uli Arta Sigalingging (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nom- mensen, 2019)
This study dealt with the development of English Reading Materials of Senior High School in SMAN 10 Medan. The objectives of this study is to develop the English reading materials for students of SMAN 10 Medan which represent the characteristics of their sociocultural environment. The research was conducted at SMAN 10 Medan. The research procedures of this study were Research and Development (R & D) that were done through three phases: 1) evaluation and need analysis, 2) materials design, and 3) materials Validation. The instruments used in this research were a documentary sheet, questionnaire sheet, and interview sheet. The data from evaluation and need analysis were analyzed by using descriptive technique and the data from expert judgment results were analyzed using quantitative data analysis. The result of this study was a coursebook of local content-based reading materials which consist of 3 genres: recount genres, descriptive genres, and narrative genres, in which each genre consists of 2 texts complete with the tasks or exercises. Based on the experts’ judgment results, the score was 87.06 which belonged to good category based on Dirgeyasa (2011), since the range is (70-89).